Pelatihan Technopreneurship melalui Social Commerce dan Branded Content Management bagi Mahasiswa Pendidikan Multimedia - ayung Candra padmasari; Deti Rostika; Fahmi Candra Permana; Feri Hidayatulloh Firmandyah (CARADDE: Jurnal Pengabdian Kepada Masyarakat, 2021)
Technopreneurship training for multimedia education study program students aims to increase creativity and foster talent, interest, entrepreneurship for digital media competence. This technopreneurship training uses lecture and practical methods, with training activities divided into 3, including 1) Providing online webinar model with experienced resource persons, 2) workshop and activity assistance, 3) live product evaluation using IGTV. The training topics taken are social commerce and branded content management techniques which are expected to be later able to help students hone entrepreneurial skills in the field of market segment management on the platform as well as the ability to branding products in the field of digital media services This training was attended by 64 students with the results of activities including 80% understanding how the process of creating a visual key for product make-up before promotion in social media, and being able to create displays and scenarios of business product material content, 90% of students were able to understand branding and re-branding. planned business products. After this training, it is hoped that in the future students will be able to manage content and market segments well, and be able to form student-level business incubators to facilitate entrepreneurial talent and interest